2018
DOI: 10.1038/s41598-018-25913-8
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation-threshold Determination and Rheological-parameters Estimation of Albumin-stabilized Nanobubbles

Abstract: Nanobubbles (NBs) are of high interest for ultrasound (US) imaging as contrast agents and therapy as cavitation nuclei. Because of their instability (Laplace pressure bubble catastrophe) and low sensitivity to US, reducing the size of commonly used microbubbles to submicron-size is not trivial. We introduce stabilized NBs in the 100–250-nm size range, manufactured by agitating human serum albumin and perfluoro-propane. These NBs were exposed to 3.34- and 5.39-MHz US, and their sensitivity to US was proven by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 87 publications
1
16
0
Order By: Relevance
“…Histologic analysis showed that NBs were retained in tumor tissue to a greater extent compared with MBs. Lafond et al (2018) recently demonstrated that their in-house fabricated albumin-based NBs, which is 100 to 250 nm in diameter were sensitive to specific acoustic pressures and could become efficient cavitation nuclei in the 3 to 5-MHz US frequency range. Acoustic passive cavitation detectors indicated that inertial cavitation threshold was lower than the commercially available MB US contrast agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologic analysis showed that NBs were retained in tumor tissue to a greater extent compared with MBs. Lafond et al (2018) recently demonstrated that their in-house fabricated albumin-based NBs, which is 100 to 250 nm in diameter were sensitive to specific acoustic pressures and could become efficient cavitation nuclei in the 3 to 5-MHz US frequency range. Acoustic passive cavitation detectors indicated that inertial cavitation threshold was lower than the commercially available MB US contrast agents.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, human serum albumin based NBs were prepared according to a previous study reported elsewhere (Lafond et al, 2018). Briefly, the air in a plastic container tube (height, 30 mm, outer diameter, 25 mm) was replaced with 15 ml of perfluoropropane (C3F8; Takachiho Chemical Industrial, Tokyo, JP) gas using a 23-gauge needle inserted through a small opening in a custom made cap.…”
Section: Preparation Of Nanobubblesmentioning
confidence: 99%
“…It is suggested that a similar cell killing or disruption phenomenon occurred in our experiments using albumin NBs. Furthermore, we previously reported that similar sized albumin-stabilized NBs (100–250 nm) were sensitive to irradiated ultrasound and were excited easily to low acoustic pressure at frequency range from 3 to 5 MHz [10]. Inertial cavitation was observed by analyzing the noise emission from the albumin NBs where the level of scattered inertial cavitation noise was greater than that of conventional microbubble ultrasound contrast agent Sonazoid®.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported on the cavitation-threshold and rheological parameters of albumin stabilized bubbles in the nanoscale range [10]. It was suggested that these nanobubbles (NBs) could be used as efficient cavitation nuclei with low intensity ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive applications of AIC, the rheological applications of AIC are relatively unexplored. In contrast to NIC and LIC, AIC produces a cavitation cloud consisting of microbubbles; thus, collective characteristics of AIC, such as a threshold of the cloud cavitation (86), are preferentially introduced instead of the cavity dynamics of a single bubble.…”
Section: A B Cmentioning
confidence: 99%